Preparation of Oil-Based Foam Gel with Nano-SiO2 as Foam Stabilizer and Evaluation of Its Performance as a Plugging Agent for Fractured Shale - Daqi Li; Fan Li; Song Deng; Jinhua Liu; Yahong Huang; Shuo Yang (Geofluids)
The development of natural fracture will lead to lost circulation, which will be likely to cause economic losses and reduce drilling efficiency. In order to solve this problem, an oil-based pressure-bearing foam gel plugging agent for fractured shale was developed. The basic components such as foaming agent, foam stabilizer, and cross-linking agent were optimized and compounded, and the basic formula of the oil-based foam gel system was 0.6%DSFA foaming agent+0.3%BPMO foaming agent+0.5%EPDM+1.5%SBS+0.05%rigid cross−linking agent DB+0.02%modified SiO2 nanoparticles. Then, the performance of the oil-based foam gel plugging agent was evaluated through core plugging experiments, and the results showed that the prepared plugging agent had good stability and plugging performance with a plugging rate of about 90%.